Cal Poly alumnus Captain Robert Gibson in space shuttle - National Aeronautics and Space Administration (NASA):::::::::
Aeronautical engineering alumnus Captain Robert Gibson, USN Retired, has flown five Space Shuttle missions: STS 41-B Challenger in 1984, STS 61-C Columbia in 1986, STS-27 Atlantis in 1988, STS-47 Endeavor in 1992, and STS-71 Atlantis in 1995. He has spent an impressive 876 hours in space.